Practical solutions for healthcare management and policy (collection) - Perednia, Douglas A.; Trusko, Brett E.; Champy, James 1942- (FTPress Delivers, 2013)
A brand new collection of state-of-the-art insights into transforming healthcare, from world-renowned experts and practitioners... now in a convenient e-format, at a great price! Making American healthcare work: 3 new eBooks get past ideology to deliver real solutions! Even after Obamacare, America's healthcare system is unsustainable and headed towards disaster. These three eBooks offer real solutions, not sterile ideology. In Overhauling America's Healthcare Machine: Stop the Bleeding and Save Trillions, leading healthcare expert and entrepreneur Douglas A. Perednia identifies the breathtaking complexity and specific inefficiencies that are driving the healthcare system towards collapse, and presents a new solution that protects patient and physician freedom, covers everyone, and won't bankrupt America. Perednia shows how to design a far simpler system: one that delivers care to everyone by drawing on the best of both market efficiency and public "universality" -- and is backed with detailed logic and objective calculations. Next, in Improving Healthcare Quality and Cost with Six Sigma, four leading experts introduce Six Sigma from the standpoint of the healthcare professional, showing exactly how to implement it successfully in real-world environments. The first 100% hands-on, start-to-finish blueprint for succeeding with Six Sigma in healthcare, this book covers every facet of Six Sigma in healthcare, demonstrating its use through examples and case studies from every area of the hospital: clinical, radiology, surgery, ICU, cardiovascular, laboratories, emergency, trauma, administrative services, staffing, billing, cafeteria, even central supply. Finally, in Reengineering Healthcare: A Manifesto for Radically Rethinking Healthcare Delivery JimChampy (" Reengineering the Corporation ") and Dr. Harry Greenspun show how reengineering methodologies can deliver breakthrough performance and efficiency improvements both within individual healthcare organizations and throughout the entire system, eliminating much of the 40%+ of U.S. healthcare costs now dedicated to administration. They demonstrate how reengineering can refocus investments on aligning quality and providing accessible care for millions more people. From world-renowned healthcare management experts Dr. Doug Perednia, Praveen Gupta, Brett E. Trusko, Carolyn Pexton , H. James Harrington, Jim Champy, and Harry Greenspun, M.D.
A compilation of three FT Press/Pearson Education titles. - Includes bibliographical references and indexes. - Online resource; title from PDF title page (Safari, viewed Feb. 11, 2013)
Keywords: Health care reform -- United States; Health reformers -- United States; Medical care -- Quality control -- Statistical methods -- United States; Medical care -- Cost control -- Statistical methods -- United States; Medical care -- Cost effectiveness -- United States; Medical care -- United States; Reengineering (Management); Services de santé; Réforme; États-Unis; Hygiénistes (Mouvement); États-Unis; Réingénierie organisationnelle; Health care reform; Health reformers; Medical care; Medical care; Cost effectiveness; Medical care; Quality control; Statistical methods; United States